Writing in the feminine in French and English Canada : a question of ethics - Carrière, Marie J., 1971- (University of Toronto Press, 2002)
This important work considers the contemporary movement of "writing in the feminine", by examining the work of five women writers from French and English Canada and the dialogue therein with feminist and psychoanalytic theory and theories of ethics. Informing the author's interpretations are the ideas of French theorists Emmanuel Levinas, Paul Ricoeur, Luce Irigaray, and Julia Kristeva, as well as American feminists Kelly Oliver and Jessica Benjamin. Marie CarriFre explores the unfolding, complex questions of sexual difference, female subjectivity, and mother-daughter relations. She also uncovers and examines the occasional breakdown of the feminist ethics postulated by Nicole Brossard, France Theoret, Di Brandt, Erin MourT, and Lola Lemire Tostevin. CarriFre views these instances of deviation not as a failure of writing in the feminine, but as an inevitability in the relatively new intellectual terrain of feminist ethics. Writing in the Feminine will be of great interest to scholars of literary theory, women's studies, and Canadian literature in French and English. As a challenging study of the connections between gender and authorship, it will also appeal to those who have a particular interest in women's literature